Straightforward Synthesis of 2‐ and 2, 8‐Substituted Tetracenes. Issue 32 (19th May 2017) - Woodward, Simon; Ackermann, Miriam; Ahirwar, Saurabh K.; Burroughs, Laurence; Garrett, Mary Robert; Ritchie, John; Shine, Jonathan; Tyril, Björk; Simpson, Kevin; Woodward, Peter
Abstract: A simple regiospecific route to otherwise problematic substituted tetracenes is described. The diverse cores ( E )‐1, 2‐Ar 1 CH2 (HOCH2 )C=C(CH2 OH)I (Ar 1 =Ph, 4‐MePh, 4‐MeOPh, 4‐FPh) and ( E )‐1, 2‐I(HOCH2 )C=C(CH2 OH)I, accessed from ultra‐low cost HOCH2 C≡CCH2 OH at multi‐gram scales, allow the synthesis of diol libraries ( E )‐1, 2‐Ar 1 CH2 (HOCH2 )C=C(CH2 OH)CH2 Ar 2 (Ar 2 =Ph, 4‐MePh, 4‐ i PrPh, 4‐MeOPh, 4‐FPh, 4‐BrPh, 4‐biphenyl, 4‐styryl; 14 examples) by efficient Negishi coupling. Copper‐catalysed aerobic oxidation cleanly provides dialdehydes ( E )‐1, 2‐Ar 1 CH2 (CHO)C=C(CHO)CH2 Ar 2, which in many cases undergo titanium(IV) chloride‐induced double Bradsher closure, providing a convenient method for the synthesis of regiochemically and analytically pure tetracenes (12 examples). The sequence is typically chromatography‐free, scalable, efficient and technically simple to carry out. Abstract : Tetracene and not hard : A procedure is reported for the preparation of substituted tetracenes from low‐cost ArCH2 Cl and HOCH2 C≡CCH2 OH. The sequence is typically chromatography‐free, scalable, efficient and technically simple to carry out.